2011
DOI: 10.1186/1556-276x-6-427
|View full text |Cite|
|
Sign up to set email alerts
|

The role of particle size of particulate nano-zinc oxide wood preservatives on termite mortality and leach resistance

Abstract: Historically most residential wood preservatives were aqueous soluble metal formulations, but recently metals ground to submicron size and dispersed in water to give particulate formulations have gained importance. In this study, the specific role nano-zinc oxide (ZnO) particle size and leach resistance plays in termite mortality resulting from exposure to particulate ZnO-treated wood was investigated. Southern yellow pine (SYP) sapwood impregnated with three concentrations of two particle sizes (30 and 70 nm)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 11 publications
2
29
0
2
Order By: Relevance
“…It should be taken into consideration that nanoparticles, especially the synthesized zinc nanopartilces, besides their insecticidal activity and also their slower effect than imidacloprid and Amitraz insecticides, have a lower risk of resistance to these nanoparticles in comparison to commercial insecticides . Clausen et al, (2011) investigated the efficiency of ZnSO 4 and ZnO nanoparticles on mortality of Reticulitermes flavipes (Kollar, 1837) (Isoptera, Rhinotermitidae). Their results confirmed that R. flavipes feeding on wood impregnated with ZnO nanoparticles, decreased to less than 4 % in comparison to control treatment.…”
Section: Figure 4: Ftir Of Synthesized Zno Nanoparticlesmentioning
confidence: 99%
“…It should be taken into consideration that nanoparticles, especially the synthesized zinc nanopartilces, besides their insecticidal activity and also their slower effect than imidacloprid and Amitraz insecticides, have a lower risk of resistance to these nanoparticles in comparison to commercial insecticides . Clausen et al, (2011) investigated the efficiency of ZnSO 4 and ZnO nanoparticles on mortality of Reticulitermes flavipes (Kollar, 1837) (Isoptera, Rhinotermitidae). Their results confirmed that R. flavipes feeding on wood impregnated with ZnO nanoparticles, decreased to less than 4 % in comparison to control treatment.…”
Section: Figure 4: Ftir Of Synthesized Zno Nanoparticlesmentioning
confidence: 99%
“…Apart from their efficacy as thermal stabilizers [22,23], their nanometric size makes them suitable for synergistic effects with organoclays, allowing combining both fire resistance performances and enhanced mechanical properties. The WPCs reinforced by nanoclay or metal oxides alone have been well documented [11,24,25]. However, to combine multiple natures of different nanoparticles into polymer matrix and hence further impregnation into wood has not been reported so far.…”
Section: Introductionmentioning
confidence: 99%
“…Several results have already been published regarding the increase in wood resistance against termites and rot fungi when treated with nano-ZnO and nano-ZnB (Manning and Laks 1998;Clausen et al 2011;Németh et al 2013). Among the benefits of applying nano-sized agents to the wood cell wall is the ability to achieve a greater degree of penetration into the cell wall (Kartal et al 2009).…”
Section: Introductionmentioning
confidence: 94%
“…However, some of those have been recently banned due to health and environmental issues. As a result, the development of environmentally friendly wood-protecting agents with low toxic impact has obtained great attention (Clausen et al 2011;Shabir Mahr et al 2013;Lykidis et al 2013) and is probably going to obtain more in the future.…”
Section: Introductionmentioning
confidence: 99%